Modelling and Analysis Study Of Plastic Waste Flow Dynamics System - Baihaqi, Muhamad Adzib (Unnes Journal of Mathematics, 2025)
Waste is closely related to people's lives today. There are various types of waste, including solid, liquid, and gas, as well as organic and inorganic waste. One of the most common types of waste generated by society is plastic waste. Plastic waste makes up a large portion of inorganic waste. One approach to recognizing the flow pattern of plastic waste is the population dynamics model. This model is considered one of the best approaches for understanding the flow of plastic waste. This process begins by creating several compartments involved in the flow of plastic waste, and then a transition diagram is formed. Next, a system of differential equations is created based on the transition diagram. This topic will also discuss the stability of the equilibrium point and numerical simulation for influential parameters.